2009
DOI: 10.2166/wh.2009.082
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of enterotoxins in environmental strains of Aeromonas hydrophila and Aeromonas jandaei

Abstract: Aeromonas species are widely distributed in aquatic environments and recent studies include the genus in the emergent pathogens group because of its frequent association with local and systemic infections in immunocompetent humans. Aiming to search for virulence genes in environmental strains of Aeromonas hydrophila and Aeromonas jandaei, we designed specific primers to detect act/hly A/aer complex and alt genes. Primers described elsewhere were used to detect ast. Eighty-seven strains previously identified us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 29 publications
5
16
1
7
Order By: Relevance
“…It has been observed in this study that the occurrence of the ast gene was restricted to the strains of A. hydrophila which were in accordance with the earlier reports (Balsalobre et al, 2009;Bin Kingombe 2010). Bin Kingombe et al (2010) speculated that an Aeromonas isolate harbouring the molecular enterotoxin profiles of control strains of A. hydrophila (ATCC 7966), an ast-positive strain, may induce not only an infection but also intoxication due to the presence of heat stable enterotoxin even if the contaminated food vehicle was heat treated.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It has been observed in this study that the occurrence of the ast gene was restricted to the strains of A. hydrophila which were in accordance with the earlier reports (Balsalobre et al, 2009;Bin Kingombe 2010). Bin Kingombe et al (2010) speculated that an Aeromonas isolate harbouring the molecular enterotoxin profiles of control strains of A. hydrophila (ATCC 7966), an ast-positive strain, may induce not only an infection but also intoxication due to the presence of heat stable enterotoxin even if the contaminated food vehicle was heat treated.…”
Section: Discussionsupporting
confidence: 93%
“…In disagreement with some of the earlier reports (Sen and Rodger, 2004;Balsalobre et al, 2009) but in accordance with the others (Pablos et al, 2009;Bin Kingombe et al, 2010;Ottaviani et al, 2011;Pinto et al, 2012), the alt gene was found to be dominant among the MPCR positive isolates of Aeromonas spp. Balsalobre et al (2009) reported that 70.7%, 97.6% and 26.8% of the A. hydrophila strains tested were positive for act/hlyA/aer, ast and alt genes, respectively, and 2.4% and 36.6% of the A. jandaei strains were positive for act/hlyA/aer complex and alt genes. Bin Kingombe et al (2010) reported that 36 % of isolates of food borne Aeromonas spp.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Compared with other class B enzymes, CphA MBL has a very specific substrate profile, being active on penem and carbapenem only, and not on penicillin and cephalosporins (Segatore et al, 1993). The distribution of cphA-related genes is species-related: they are mainly found in isolates of A. hydrophila, A. veronii and Aeromonas jandaei, but not in A. caviae (Balsalobre et al, 2009;Rossolini et al, 1995). However, CphA MBL production is not easily detected by in vitro susceptibility testing unless using large inocula.…”
Section: Introductionmentioning
confidence: 99%